Does Brazil need a notwithstanding clause? - Diniz Araújo, Luiz Henrique (Revista de Investigações Constitucionais, 2022)
In the last decade, Brazilian Supreme Court has been playing a very important role in the democratic process, raising concerns on judicial activism and on the so-called “juristocracy”. One of the ideas that comes up to tackle those issues is the adoption of a Canadian-style notwithstanding clause. Revolving the notwithstanding clause features and its practical exercise in Canada, the paper contends that it is not suitable for Brazilian constitutional system of strong judicial review. It also demonstrates that such a constitutional instrument would not help the improvement of institutional dialogues between the judiciary and legislative branches nor effectively remedy hints of judicial activism.